Mycotoxin Contamination in the Food Chain - Eny Martindah; Sjamsul Bahri (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Mycotoxins contamination in animal feed is harmful to livestock and leads to residues, such as aflatoxin and its metabolites (aflatoxin M1, aflatoxicol, aflatoxin Q1 and aflatoxin P1) which are deposited in meat, milk, and eggs. The existence of mycotoxins has been widespread; and mycotoxin is the most important contaminant in the food chain because it has implications for human health. Mold growth and mycotoxin production mainly depend on the weather, such as warm temperatures (28-31°C) and high humidity (60-90%). Some types of mold can produce more than one type of mycotoxin and some mycotoxins can be produced by more than one species of fungi. Mycotoxins, especially aflatoxin, fumonisin, zearalenone, ochratoxin, deoxynivalenol, and T2 toxin present in feed and feedstuffs that have to be controlled. Mycotoxins are not only harmful to the health of consumers, but will also reduce the quality of the product that is contaminated, and cause economic losses. The risk of mycotoxin contamination in animal feed could be reduced by inhibiting the mould growth and toxin production, through crop rotation, using proper fungicides, and applying regulation of mycotoxins maximum limit in feed and food in order to prevent any danger to public health.